The Legal status of Vaccine Manufacturers' Liability: A Comparative Study - Raad Spahi, Researcher. Ghanem; Abdulridha Ali Al-Fardan, Assist. Prof. Dr. Munqith (Basra studies journal, 2024)
The topic of civil liability arising from vaccine damages is one of the important and delicate issues, given its close connection to individuals' physical safety. Therefore, we have examined the legal adaptation of liability and found the differences regarding the nature of vaccine manufacturer liability. Some have emphasized contractual liability, while others have argued for liability based on negligence, which is what Iraqi law has adopted. This was done through the adoption of an analytical comparative study among the legislation of four countries: Iraq, Egypt, France, and Lebanon, while referring to opinions and judicial precedents wherever possible.